Overview of Patient Satisfaction with the Application of Mobile JKN Using EUCS Method - Bahrul Ilmi; Muhammad Al Ashari (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2026)
Mobile JKN is a digital application developed by BPJS Kesehatan to facilitate participants in accessing health services quickly and efficiently. Despite its widespread use, users still experience various obstacles, including difficulties in using application features, slow system access, and dissatisfaction with the information provided. Therefore, evaluating user satisfaction is important to assess the quality of the Mobile JKN application from the patient’s perspective. This study aimed to describe patient satisfaction with the Mobile JKN application using the End User Computing Satisfaction (EUCS) method at RSI Ibnu Sina Padang. This quantitative descriptive study was conducted at RSI Ibnu Sina Padang in 2025. The study population consisted of outpatients who used the Mobile JKN application. A total of 120 respondents were selected using accidental sampling. Data were collected using an EUCS questionnaire covering five dimensions: content, accuracy, format, ease of use, and timeliness. Data were analyzed using univariate analysis and presented as frequency distributions and percentages. The results showed that 65.8% of respondents were satisfied with the implementation of Mobile JKN. Based on the EUCS dimensions, satisfaction levels were 70.0% for content, 68.3% for accuracy, 66.7% for format, 75.0% for ease of use, and 63.3% for timeliness. Ease of use received the highest score, while timeliness received the lowest. In conclusion, most patients were satisfied with the Mobile JKN application at RSI Ibnu Sina Padang. Continuous improvements, particularly in timeliness and system response speed, are needed to enhance user experience and service quality.